Effectiveness of Aldicurb Against Insegt Pests of Brinjal Alongwith its Uptake and Residues - Gupta, H C; Mehta, S C; Pareek, B L (Annals of Arid Zone, 2016)
Side dressing of aldiearb granules @ 0.5, 1.0 and 1.5 kg ai/ha not on1y protected the brinjal crop against jassids and fruit borer but also stimulated the crop growth. Cost: benefit ratios obtained for the three doses were I:13, 1:7 and 1:’. respectively. The application of aldicarb at the three leves of active ingredient. correspondingly gave deposits in soil to the tune of 8, 12 and 17 ppm. respectively, more than 55% of which was lost in 7 days, about 75% in 15 days and almost cent per cent dissipation took place in 30 days. The Translocation of the insecticide from soil to leaves and fruits of hrinjal was obselved to occur between 3 and 7 days. At the final harvest. aldicarb residues in fruits were above the tolerance limit of 0.2 ppm except in the lowest IreatmeR dosage of 0.5 kg ai / ha.